Contextualing a Tourism Development Alternative for Argentina: A Proposal for Community Based Diffused Tourism - Mtapuri, Oliver; Giampiccoli, Andrea (Journal of Tourism, Sustainability and Well-being, 2021)
This conceptual paper proposes using a new Community-based diffused tourism (CBDT) model, which is based on the consolidation of Community-based tourism and ‘Albergo diffuso’ (AD). CBDT is a model of tourism development that is dispersed over a given territory. It consists of an assemblage of hospitality facilities, social cohesion, and commonality of aspirations to empower disadvantaged communities and develop local economies for profitsharing tourism. The Social and Solidarity Economy of Argentina presents possibilities upon which CBDT can be formed. This opens up chances to describe culture and community in local terms. The CBDT is a confluence of minds, services, resources, and capacities serving a common purpose for the common good. The CBDT model has the characteristics of ownership/control residing with the local community, is geographical/space-specific, and boasts several typologies, such as neighbourhood-based CBDT, street-based CBDT, and ‘building’-based CBDT involving inhabited and uninhabited spaces.